Critical review of issues in financing of small and marginal farmers of Kashmir : a case for Islamic value - chain finance - Hussain, Horiya (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
Agriculture and farming has been the oldest primary occupation of man. Besides providing for livelihood for the people, it ensures food security and sustainability of a nation. In most developing economies majority of agriculture holdings are small. In India, the total number of small and marginal farm land holdings is about 85% of the total operational holdings under agriculture. Correspondingly, in the Kashmir division of the state of Jammu & Kashmir, India, majority of agriculture land holdings are categorized as marginal and small. The total percentage of cultivators and agriculture labourers is 39.79% in relation to the total worker population, portraying the dependence on agriculture of majority of the rural Kashmiri population. These small and marginal farmers face a number of issues such as lack of irrigation, road, transportation, storage facilities, lack of proper fertilizers, pesticides, agricultural machinery, sparse coverage of arable land, and limited formal credit availability. These issues in-turn affect the food productivity and agriculture sustainability of the nation. Consequently, small farmers' income growth, development and sustainability are also affected by the lack of infrastructure, market and credit. Among the prominent issues identified for small farmer growth and development is timely, affordable and effective credit facility. As such, this research appraises the value chain financing approach which comprehensively provides for timely and effective credit at each stage of the value chain for small farmers. Moreover, the use of Islamic financial contracts for value chain financing for small farmers is evaluated. Islamic financial contracts share the risk sharing approach innate to value chain financing. The value chain financing approaches the farmer as an entrepreneur in the agriculture business sector rather than an individual entity isolated from the real economic scenario, as evident in current conventional financing practices. As such, the three characteristics of flexibility, proximity and representativeness are common to Islamic finance as well as value chain financing that can lead to sustainable and comprehensive development of small and marginal farmers of Kashmir.